The equilibrium liquidus temperatures of rhenium–carbon, platinum–carbon and cobalt–carbon eutectic alloys. (25th May 2017) - Lowe, D H; Todd, A D W; Van den Bossche, R; Bloembergen, P; Anhalt, K; Ballico, M; Bourson, F; Briaudeau, S; Campos, J; Cox, M G; del Campo, D; Dury, M R; et al.
Abstract: The eutectic alloys rhenium–carbon, platinum–carbon and cobalt–carbon have been proposed as reference standards for thermometry, with temperature and uncertainty values specified within the mise en pratique of the definition of the kelvin. These alloys have been investigated in a collaboration of eleven national measurement institutes and laboratories. Published results reported the point-of-inflection in the melting curve with extremely low uncertainties. However, to be considered as standards it is necessary to stipulate what phenomenon a temperature value has been ascribed to; specifically, this should be a thermodynamic state. Therefore, the data have been further evaluated and the equilibrium liquidus temperatures determined based on a consideration of limits and assuming a rectangular probability distribution. The values are: for rhenium–carbon 2747.91  ±  0.44 K, for platinum–carbon 2011.50  ±  0.22 K and for cobalt–carbon 1597.48  ±  0.14 K, with uncertainties at approximately a 95% coverage probability. It is proposed that these values could be used as the basis of thermodynamic temperature measurement at high temperatures (above 1300 K).